Strategi Komunikasi Humas Dalam Pelayanan Prima Pada Dinas Perpustakaan Dan Kearsipan Kabupaten Musi Banyuasin - Wulandari; Henny Yusalia; M. Mifta Farid (Journal of Media and Communication | E-ISSN : 3063-9581, 2025)
In this increasingly advanced digital era, library public relations requires a communication strategy in providing excellent service to attract visitors, because nowadays they are more interested in finding information on the internet than reading books. Therefore, an effective communication strategy is needed from the Musi Banyuasin Regency Library and Archives Office to introduce its services and collections to the public. This research aims to find out the communication strategy of public relations in improving excellent service to library visitors and to find out the public response to the excellent service provided by the Library and Archives Office of Musi Banyuasin Regency. This research uses a qualitative approach, where the data is obtained through observation, interview and documentation methods. The results showed that the Office of Libraries and Archives of Musi Banyuasin Regency has provided excellent service to visitors by applying the five dimensions of excellent service namely reliability, responsiveness, assurance, empathy and providing various facilities that make visitors feel comfortable. In addition, the Musi Banyuasin Regency Library and Archives Office has received positive and constructive feedback on the excellent service they have provided. So that the response from the public makes the library want to always provide the best services and collections for the public.